Literary, journalistic activity of Northern Azerbaijan writers in Southern Azerbaijan and the embodiment of a divided motherland idea in their creation - Huseyinova, Arzu Huseyin (International Journal of Psychosocial Rehabilitation, 2020)
Literary – journalistic works are resaerched in the article that played an important role in social – political, literary processes influenced to the unit motherland idea in the Soviet Azerbaijan and Southern Azerbaijan in the 40th years of 20th centure. Author comments about the influence of creative intellectuals from the Soviet Azerbaijan to the national consciousness and self-understanding by press organs in Southern Azerbaijan, topic directions of “Azerbaijan” journal (this journal had been broadcasted in Baku especially for South), their fight for the interests of unit Azerbaijan, an author researches idea and influence power of the works in philological point of view, and explains turning of unit motherland idea into social consciousness